Human factors in hydrogen storage: An analysis of safety implications - Bulat, Hasan Huseyin; Kaymakci, Ozguer Turay; Ilhan, Haci (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
In recent years, due to the growing interest in sustainable energy, technologies utilizing hydrogen have become increasingly significant. However, the potential risks accompanying this progress should not be overlooked. This study makes a significant contribution to the literature by detailing the effects of human error in hydrogen storage systems through both qualitative and quantitative analyses. Our work aims to enhance awareness and provide new perspectives for future research by quantitatively demonstrating the impact of human error on system safety and performance. This approach lays the groundwork for developing new strategies to make hydrogen storage systems safer and more efficient. In our proposed model, questions related to the system were directed to 10 experts to better understand the uncertain effects of human errors on safety. Based on the responses received, a method has been suggested to form fuzzy numbers representing risks that may arise due to human errors. Referring to a hydrogen storage system actively utilized in industry, a fuzzy fault tree was prepared for the highest risk, namely hydrogen explosion, and these fuzzy numbers were evaluated within the fault tree to analyze their impact on safety. As a result of this analysis, no change was observed in the SIL level, and only a minimal difference was seen in the PFDAvg value. In this context, the fault tree results indicate that the effect of human-induced errors on the system's safety is limited. This study clearly emphasizes the critical importance of safety management for hydrogen storage systems and the standards and regulations that need to be considered in this field.
Keywords: Functional safety; Hydrogen storage; Fuzzy fault tree analysis; QUANTITATIVE RISK-ASSESSMENT; FUELING STATIONS; SYSTEMS; Chemistry; Electrochemistry; Energy & Fuels